The Relationship Between Length of Employment and Job Position With Low Back Pain Complaints Among Civil Servants at Batauga Public Health Center, South Buton Regency - Hasiu, Teti Susliyanti; Prasetyo, Budi; Asrianto, La Ode; Amrullah, Rita (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
This study aims to analyze the relationship between length of service and working position with complaints of low back pain among Civil Servants at Batauga Health Center, South Buton Regency. All employees were involved as respondents by filling out questionnaires, so the data collected was primary data. The sampling technique used was total sampling, meaning the entire population was included in the study. Data were analyzed using univariate and bivariate approaches to identify the distribution of variables and the relationship between them. The findings show that most respondents had relatively short working years, while only a small proportion had longer service periods. In terms of working position, many respondents were still in less ergonomic positions, although some had better working positions. Regarding low back pain, the majority of respondents reported no complaints, while a number of others experienced such discomfort. The statistical analysis revealed a significant relationship between length of service and complaints of low back pain. In addition, there was also a significant correlation between working position and low back pain complaints. These results highlight that both length of service and working position contribute to the risk of health problems among employees.